Structure-Activity Relationships of the Peptide Kappa Opioid Receptor Antagonist Zyklophin - Joshi, Anand A. (J Med Chem, 2015)
The dynorphin (Dyn) A analog zyklophin ([N-benzyl-Tyr(1)-cyclo(D-Asp(5),Dap(8))]dynorphin A(1-11)NH(2)) is a kappa opioid receptor (KOR) selective antagonist in vitro, is active in vivo and antagonizes KOR in the CNS after systemic administration. Hence, we synthesized zyklophin analogs to explore the structure-activity relationships of this peptide. The synthesis of selected analogs required modification to introduce the N-terminal amino acid due to poor solubility and/or to avoid epimerization of this residue. Among the N-terminal modifications the N-phenethyl and the N-cyclopropylmethyl substitutions resulted in the analogs with the highest KOR affinities. Pharmacological results for the alanine-substituted analogs indicated that Phe(4) and Arg(6), but interestingly not the Tyr(1), phenol are important for zyklophin’s KOR affinity, and Arg(7) was important for KOR antagonist activity. In the GTPγS assay while all of the cyclic analogs exhibited negligible KOR efficacy, the N-phenethyl-Tyr(1), N-CPM-Tyr(1) and the N-benzyl-Phe(1) analogs were 8- to 24-fold more potent KOR antagonists than zyklophin.